Repair of damaged end regions of PC beams using externally bonded FRP shear reinforcement. (1st September 2017) - Shaw, Ian; Andrawes, Bassem
Highlights: Mortar repairs for damaged ends of PC bridge girders are structurally insufficient. Externally bonded FRP can restore the shear strength of PC beam with localized damaged end regions. CFRP is more effective than GFRP in restoring shear strength and stiffness of PC beams with damaged ends. Abstract: Fiber reinforced polymer (FRP) composites have emerged as a lightweight and efficient repair and retrofit material for many concrete infrastructure applications. Externally bonded FRP laminates have been shown to be an effective material when used as supplemental flexural and shear reinforcement for reinforced concrete and prestressed concrete beams. One problem afflicting bridge girders is the deterioration of the beam ends due to deicing salt exposure, thus reducing their shear strength. In this study, concrete cover damages are imposed on small scale prestressed concrete beams, which are tested in three-point bending to determine the effect of this type of damage on the shear capacity of the beams. A quick setting mortar repair is used to replace the damaged cover concrete and test its ability to recover the shear strength of the beam. The results show the mortar repair alone is insufficient in regaining the beam's original strength and stiffness. Externally bonded glass and carbon FRP laminates are used as shear reinforcement in conjunction with the mortar repair to recover the strength of the beam. CFRP laminates were superior to GFRP laminates in regaining and exceeding the stiffness and strength of the undamaged beam for this application.